2018
DOI: 10.1111/ajt.14661
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effect of the gut microbiome altered by high-dose tacrolimus in mice

Abstract: The alterations induced in gut microbiota by tacrolimus may affect immune function and organ transplantation. Mice were treated with high-dose tacrolimus for 14 days. The fecal microbiota were analyzed by pyrosequencing the 16S rRNA genes, and the effect on metabolism was predicted using the sequence data. The subgroups of T cells in the serum, gut-associated lymphoid tissue, and draining lymph nodes were determined by flow cytometry. Tacrolimus treatment significantly altered the relative abundance of Allobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 31 publications
10
75
0
Order By: Relevance
“…79 Calcineurin inhibitors affect the intestinal microbiome and intestinal barrier. 80 Longitudinal analysis of gut microbiota pre-and post-LT showed improvement in diversity after 6 months. 81 Interestingly, the pace of resolution of pretransplant perturbations in microbiota composition was negatively correlated with the burden of multidrug resistant organisms.…”
Section: Composition and Functional Changes In Microbiota In Patientsmentioning
confidence: 98%
“…79 Calcineurin inhibitors affect the intestinal microbiome and intestinal barrier. 80 Longitudinal analysis of gut microbiota pre-and post-LT showed improvement in diversity after 6 months. 81 Interestingly, the pace of resolution of pretransplant perturbations in microbiota composition was negatively correlated with the burden of multidrug resistant organisms.…”
Section: Composition and Functional Changes In Microbiota In Patientsmentioning
confidence: 98%
“…Therefore, the mechanism of PTDM development after tacrolimus therapy is partly related to the direct toxicity of tacrolimus 12 . On the other hand, in our previous study, we reported that tacrolimus altered the composition and taxa of the gut microbiota, which resulted in immunoregulatory functions of colonic and systemic immune responses and an increased allograft survival rate 13 . Whether the effect on the tacrolimus‐induced gut microbiota might cause a greater tendency to PTDM is currently unclear.…”
Section: Introductionmentioning
confidence: 94%
“…In the same study, the transfer of the commensal Bifidobacterium pseudolongum alone was sufficient to reduce cardiac graft inflammation and fibrosis . The potential of adjuvant approaches combining standard immunosuppression with microbiota‐targeted interventions was exemplified by an animal study, where the combination of the tacrolimus with FMT resulted in increased skin allograft survival …”
Section: Role Of the Gut Microbiota In Transplantationmentioning
confidence: 95%